2001
DOI: 10.1023/a:1014057407251
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Eucheuma serra agglutinin (ESA) derived from a marine red alga, Eucheuma serra, is a lectin that specifically binds to mannose-rich carbohydrate chains. ESA is a monomeric molecule, with a molecular weight of29,000. ESA induced cell death against several cancer cell lines, such as colon cancer Colo201 cells and cervix cancer HeLa cells. DNA ladder detection and the induction of caspase-3 activity suggested that the cell death induced by ESA against cancer cells was apoptosis. ESA bound to the cell surface of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 7 publications
1
28
0
Order By: Relevance
“…As shown previously [4], ESA hardly binds to normal cells. If ESA-FITC binding to cells occurs, a rightward shift of the flow cyotometric curve is expected.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…As shown previously [4], ESA hardly binds to normal cells. If ESA-FITC binding to cells occurs, a rightward shift of the flow cyotometric curve is expected.…”
Section: Resultssupporting
confidence: 81%
“…Previously, we have already demonstrated that ESA induces apoptosis in carcinoma cells [4]. The findings presented above about the inhibition of sarcoma cell proliferation (see Section 3.1.)…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…Such a diameter of a particle of the carbon mesocell is uniformly controlled to 400 nm or less, the carbon mesocell can also be expected as a biotechnological material to replace the spherical endoplasmic reticulum [8] of pinpoint delivery. Furthermore, if several microns comparatively big carbon mesocells are manufactured, it is considered that it can be used as a lubricous material in the tribology, and that fullerence is very small and less effective.…”
Section: Resultsmentioning
confidence: 99%